Validity of student creativity test instruments on energy and its changes for junior high school students - Hardila, Dilva; Vebrianto, Rian (Universitas Wiralodra, 2024)
Science subjects not only master various types of knowledge, such as facts, concepts, or principles, but are also a process of discovery. In this era, creativity has become mandatory in schools and universities. This is also mentioned in relevant research which explains that creative thinking in learning is very important, especially in science learning. Therefore, the aim of this research is to create a test that improves students' creative abilities, with special emphasis on energy and its changes, which is one of the subjects in the field of natural sciences. This research is development research (R&D) using the ADDIE model. The results of data analysis show that the test questions have quite high validity and reliability, the difficulty index shows that the test questions are in the quite good category. Furthermore, with a question reliability index ranging from 0.69 > 0.60 on high criteria, this test instrument can be said to produce the same results if tested at a different time or place with reliable criteria. Based on the results of the data analysis, it was concluded that the test questions developed were suitable for use with students to measure students' creative abilities in the matter of energy and its changes.